Failure Investigation of a Steel Pipe - Abdul Rahman Bin Abdul Halim Koh, Abdul Rahman (Universiti Teknologi Petronas, 2008)
This paper presents an investigation of a steel pipe failure. The pipe was retrieved from a car cooling system The failure involved some pin holes that cause leakage of liquid coolant of radiator. The corrosion attacks the internal wall of the pipe to the outside and caused the pin hole. The objectives of this project are to find to cause of radiator pipe failure, to apply the knowledge as a mechanical engineering student as well as to recommend the way to improve the pipe service in radiator. In this paper, the pipe failure is investigated by examination the failed steel pipe using several methods such as, visual inspection, microscopy inspection, scanning electron microscopy inspection and energy dispersive spectrographic inspection. A series of failure analyses and nondestructive examination were performed to identify the possible causes of the failures. From the examination, it shows that the sample experienced internal corrosion before the major failure happened. Thorough failure investigation is essential for the effective of radiator system and reliability of the engine. The pin holes are highly probable occurred from internal part of the pipe due to corrosive level of radiator liquid coolant.